Circulating c-Met–Expressing Memory T Cells Define Cardiac Autoimmunity. Issue 25 (23rd November 2022) - Fanti, Silvia; Stephenson, Edward; Rocha-Vieira, Etel; Protonotarios, Alexandros; Kanoni, Stavroula; Shahaj, Eriomina; Longhi, M. Paula; Vyas, Vishal S.; Dyer, Carlene; Pontarini, Elena; Asimaki, Angeliki; Bueno-Beti, Carlos; et al.
Abstract : Background: Autoimmunity is increasingly recognized as a key contributing factor in heart muscle diseases. The functional features of cardiac autoimmunity in humans remain undefined because of the challenge of studying immune responses in situ. We previously described a subset of c-mesenchymal epithelial transition factor (c-Met)–expressing (c-Met + ) memory T lymphocytes that preferentially migrate to cardiac tissue in mice and humans. Methods: In-depth phenotyping of peripheral blood T cells, including c-Met + T cells, was undertaken in groups of patients with inflammatory and noninflammatory cardiomyopathies, patients with noncardiac autoimmunity, and healthy controls. Validation studies were carried out using human cardiac tissue and in an experimental model of cardiac inflammation. Results: We show that c-Met + T cells are selectively increased in the circulation and in the myocardium of patients with inflammatory cardiomyopathies. The phenotype and function of c-Met + T cells are distinct from those of c-Met–negative (c-Met − ) T cells, including preferential proliferation to cardiac myosin and coproduction of multiple cytokines (interleukin-4, interleukin-17, and interleukin-22). Furthermore, circulating c-Met + T cell subpopulations in different heart muscle diseases identify distinct and overlapping mechanisms of heart inflammation. In experimental autoimmune myocarditis, elevations in autoantigen-specific c-Met + T cells in peripheral blood mark the loss of immune tolerance to the heart. Disease development can be halted by pharmacologic c-Met inhibition, indicating a causative role for c-Met + T cells. Conclusions: Our study demonstrates that the detection of circulating c-Met + T cells may have use in the diagnosis and monitoring of adaptive cardiac inflammation and definition of new targets for therapeutic intervention when cardiac autoimmunity causes or contributes to progressive cardiac injury.